STUDI KELAYAKAN AIR TERJUN NGGEMBOR SEBAGAI DESTINASI WISATA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA JATIMULYO, KECAMATAN GIRIMULYO, KABUPATEN KULONPROGO, YOGYAKARTA - Syamsu, Moch. Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
One of many ecotourism potentials that exist in Indonesia is natural object that can be utilized by the community for watering purposes as well as for the tourist attraction, namely waterfalls. One of developing natural tourist attraction is Nggembor Waterfall. This waterfall is located in Dusun Banyunganti, Jatimulyo Village, Girimulyo District, Kulon Progo Regency, Special Province of Yogyakarta. This research used qualitative method with SWOT analysis. From the results of the study, it was found that Nggembor Waterfall is worthy as a tourist destination, which is expected to improve the economy of the community. Keywords: Waterfall, Tourism Destination, Ecotourism